Blood pressure and metabolic efficacy of fixed-dose combination of perindopril and indapamide in everyday practice. (September 2013) - Farsang, Csaba; ,
Abstract The aim of the PICASSO study was to evaluate the efficacy and safety of fixed-dose perindopril 10 mg/indapamide 2.5 mg in everyday medical practice. In this 3-month, open-label, observational study, outpatients with primary hypertension who did not reach the blood pressure goal (< 140/90 mmHg) with antihypertensive treatment were enrolled if their treating physician had planned, as part of their ongoing therapy, to switch them to fixed-dose perindopril 10 mg/indapamide 2.5 mg. Blood pressure, heart rate, and metabolic parameters and – optionally – ambulatory blood pressure were measured. Data from 9257 patients were evaluated. Over the course of 3 months, mean blood pressure decreased from 159/93 mmHg to 132/80 mmHg (p < 0.001) and heart rate decreased from 79 to 73 beats/min (p < 0.001). The target blood pressure was reached by 72.7% of patients. Reductions in total cholesterol, low-density lipoprotein-cholesterol (LDL-c), triglycerides, fasting glucose and uric acid levels were clinically significant. Blood levels of high-density lipoprotein-cholesterol (HDL-c), sodium and potassium remained unchanged. Beneficial changes in metabolic parameters were primarily attributed to the reduction in therapy with drugs with unfavourable metabolic profiles (thiazides and beta-blockers). Perindopril/indapamide is an effective and safe antihypertensive treatment in everyday medical practice.